Simultaneous delivery of hydrophobic small molecules and siRNA using Sterosomes to direct mesenchymal stem cell differentiation for bone repair. (August 2017) - Cui, Zhong-Kai; Sun, Justin A.; Baljon, Jessalyn J.; Fan, Jiabing; Kim, Soyon; Wu, Benjamin M.; Aghaloo, Tara; Lee, Min
Graphical abstract: Abstract: The use of small molecular drugs with gene manipulation offers synergistic therapeutic efficacy by targeting multiple signaling pathways for combined treatment. Stimulation of mesenchymal stem cells (MSCs) with osteoinductive small molecule phenamil combined with suppression of noggin is a promising therapeutic strategy that increases bone morphogenetic protein (BMP) signaling and bone repair. Our cationic Sterosome formulated with stearylamine (SA) and cholesterol (Chol) is an attractive co-delivery system that not only forms stable complexes with small interfering RNA (siRNA) molecules but also solubilizes hydrophobic small molecules in a single vehicle, for directing stem cell differentiation. Herein, we demonstrate the ability of SA/Chol Sterosomes to simultaneously deliver hydrophobic small molecule phenamil and noggin-directed siRNA to enhance osteogenic differentiation of MSCs both in in vitro two- and three-dimensional settings as well as in a mouse calvarial defect model. These results suggest a novel liposomal platform to simultaneously deliver therapeutic genes and small molecules for combined therapy. Statement of Significance: Application of phenamil, a small molecular bone morphogenetic protein (BMP) stimulator, combined with suppression of natural BMP antagonists such as noggin is a promising therapeutic strategy to enhance bone regeneration. Here, we present a novel strategy to co-deliver hydrophobic small molecule phenamil and noggin-targeted siRNA via cationic Sterosomes formed with stearylamine (SA) and high content of cholesterol (Chol) to enhance osteogenesis and bone repair. SA/Chol Sterosomes demonstrated high phenamil encapsulation efficiency, supported sustained release of encapsulated drugs, and significantly reduced drug dose requirements to induce osteogenic differentiation of mesenchymal stem cells (MSCs). Simultaneous deliver of phenamil and noggin siRNA in a single vehicle synergistically enhanced MSC osteogenesis and calvarial bone repair. This study suggests a new non-phospholipid liposomal formulation to simultaneously deliver small molecules and therapeutic genes for combined treatment.